Діагностика професійно важливих якостей керівника вищого військового навчального закладу - Солодовник (Бутенко), Тетяна Олександрівна; Артюшенко, Олена Вікторівна (НТУ "ХПІ", 2014)
У статті визначено професійно важливі якості керівника вищого військового навчального закладу та проаналізовано методи їх діагностування. Розкрито специфіку професійної діяльності військових та важливість професійно важливих якостей для управління вищим військовим навчальним закладом.

In the article important qualities of leader of higher military educational establishment are certain professionally and the methods of their diagnosticating are analysed. The specific of professional activity is exposed soldiery and importance professionally important qualities for a management by higher military educational establishment.
Diagnostics professionally important qualities of leader of higher military educational establishment
Keywords: діяльність професійна; підготовка професійна; діяльність управлінська; professional activity; professional preparation; administrative activity; management